Cloning of pe11 (LipX, Rv1169c) gene of Mycobacterium tuberculosis Beijing strain to pcDNA3.1 plasmid vector - Supardi, Lulut Azmi; Rukmana, Andriansjah; Sjatha, Fithriyah (Makara Journal of Science, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. It is a persistent global health problem with a high mortality rate. Currently, TB is controlled by administering the Bacillus Calmette-Guerin (BCG) vaccine, but the effectiveness of its protection varies among individuals in a population. The pe/ppe gene family comprises a typical group of genes that play a role in avoiding the host immune response and inducing persistent TB infection. Based on in silico analysis, the pe11 gene has estimated immunogenicity and potential as a TB seed vaccine candidate. The pe11 gene from an Indonesian isolate of an M. tuberculosis Beijing strain was amplified by polymerase chain reaction (PCR) and inserted into the mammalian expression vector pcDNA3.1. The recombinant vector pcDNA3.1-pe11 was used to transform Top10 competent Escherichia coli. Clones from the transformation were subjected to colony PCR to confirm the direction of the insert. Sequencing was performed to confirm the correctness of the insert sequence. In this study, the pe11 gene was successfully cloned into the pcDNA3.1 vector in the correct direction to assure PE11 expression. No mutations were found in the pe11 gene insert, compared with the M. tuberculosis H37Rv sequence as the standard. A pcDNA3.1 vector containing the pe11 gene derived from an M. tuberculosis Beijing strain was successfully constructed.